The presence of Plasmodium malariae and Plasmodium knowlesi in near malaria elimination setting in western Indonesia - Irbah Rea Alvieda Nainggolan; Rycha Dwi Syafutri; Monica Nadya Sinambela; Clara Devina; Handayani; Beby Syofiani Hasibuan; Sriwipa Chuangchaiya; Paul C. S. Divis; Zulkarnain Md Idris; Ranti Permatasari; Inke Nadia Diniyanti Lubis (Malaria Journal, 2022)
Abstract Background Indonesia is progressing towards malaria elimination. To achieve this goal, intervention measures must be addressed to cover all Plasmodium species. Comprehensive control measures and surveillance programmes must be intensified. This study aims to determine the prevalence of microscopic and submicroscopic malaria in Langkat district, North Sumatera Province, Indonesia. Methods A cross-sectional survey was conducted in six villages in Langkat district, North Sumatera Province in June 2019. Data were recorded using a standardized questionnaire. Finger pricked blood samples were obtained for malaria examination using rapid diagnostic test, thick and thin blood smears, and polymerase chain reaction. Results A total of 342 individuals were included in the study. Of them, one (0.3%) had a microscopic Plasmodium malariae infection, no positive RDT examination, and three (0.9%) were positive for P. malariae (n = 1) and Plasmodium knowlesi (n = 2). The distribution of bed net ownership was owned by 40% of the study participants. The participants had a house within a radius of 100–500 m from the forest (86.3%) and had the housing material of cement floor (56.1%), a tin roof (82.2%), wooden wall (35.7%), bamboo wall (28.1%), and brick wall (21.6%). Conclusion Malaria incidence has substantially decreased in Langkat, North Sumatera, Indonesia. However, submicroscopic infection remains in the population and may contribute to further transmission. Surveillance should include the detection of microscopic undetected parasites, to enable the achievement of malaria elimination.